PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP IPAS DI SEKOLAH DASAR - Suci Fauziah Rahma; Yoesrina Novia Vini Syafitri; Dewi Fitriani; Puput; Aura Putri Salsabillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low understanding of elementary school students' science concepts caused by the teacher-centered learning process and the lack of use of interesting learning media so that students are less active in understanding the material. One effort that can be done to improve students' understanding of concepts is through the application of the Problem Based Learning (PBL) model assisted by animated videos. This study aims to determine the learning process using the Problem Based Learning (PBL) model assisted by animated videos and its effect on elementary school students' understanding of science concepts. This study uses a quantitative approach with an experimental method (quasi-experimental design) using a nonequivalent control group design. Data collection techniques are carried out through tests and observations. Based on the results of the study, it was found that the average pretest score of the experimental class was 50.64, increasing to 75.82 in the posttest, while the average pretest score of the control class was 47.50, increasing to 71.07 in the posttest. The results of the hypothesis test using the Independent Samples t-Test showed a significance value of 0.014 < 0.05, indicating that the Problem-Based Learning (PBL) model assisted by animated videos has an effect on elementary school students' understanding of science concepts. Based on the results of the study, it can be concluded that the application of the Problem-Based Learning (PBL) model assisted by animated videos can improve students' understanding of science concepts.